2016
DOI: 10.1016/j.arth.2015.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Good vs Poor Results After Total Hip Arthroplasty: An Analysis Method Using Implant and Anatomic Parameters With the EOS Imaging System

Abstract: With the EOS system, a large cohort can be studied relatively quickly and at low dose, which could lead to patient-specific guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
0
14
0
2
Order By: Relevance
“…However, with progressive ageing of the spine, this compensatory mechanism becomes ineffective and the patient starts to become sagittally imbalanced as shown by the excessively anterior C7pl (‘decompensated stage’). 8 , 13 A sagittal imbalance substantially affects the quality of life and can be clinically deleterious 14 - 16 because, when standing, the patient has to hyperextend the neck in order to keep a horizontal sightline, and the hips are at risk of OA secondary to aberrant standing functional acetabular orientation, under-coverage of the femoral head anteriorly and posterior impingement. 17 , 18 With THA, implants would therefore be at a higher risk of failure, notably through complications related to edge-loading and anterior prosthetic instability.…”
Section: Abnormal Shrmentioning
confidence: 99%
“…However, with progressive ageing of the spine, this compensatory mechanism becomes ineffective and the patient starts to become sagittally imbalanced as shown by the excessively anterior C7pl (‘decompensated stage’). 8 , 13 A sagittal imbalance substantially affects the quality of life and can be clinically deleterious 14 - 16 because, when standing, the patient has to hyperextend the neck in order to keep a horizontal sightline, and the hips are at risk of OA secondary to aberrant standing functional acetabular orientation, under-coverage of the femoral head anteriorly and posterior impingement. 17 , 18 With THA, implants would therefore be at a higher risk of failure, notably through complications related to edge-loading and anterior prosthetic instability.…”
Section: Abnormal Shrmentioning
confidence: 99%
“…A number of authors have noted similar findings. Bendaya et al 16 noted that single plane image analysis in non-functional positions fails to accurately measure acetabular cup positioning. Multiple authors have identified difficulty in measuring anteversion on an AP pelvic radiograph, and Kalteis et al 6,17 noted the potential for large error in measuring anteversion ranging from −16.6° to + 29.8°.…”
Section: Discussionmentioning
confidence: 99%
“…Images and associated 3D semi-automatic reconstructions were derived from EOS biplanar radiographs (Dubousset et al 2010) (EOS Imaging, Paris, France) of 120 subjects (57 females, 63 males) collected in previous studies (Surets et al 2005;Chaibi et al 2012;Quijano et al 2013;Pillet et al 2014;Sangeux et al 2014;Ohl et al 2015;Amabile et al 2016;Bendaya et al 2016;Zhang et al 2016;Ghostine et al 2017). Ages, weights and heights were comprised between 20 and 76 years old, 42 and 120 kg and 150 and 190 cm.…”
Section: Biplanar X-ray Acquisition and 3d Reconstruction Of The Pelvismentioning
confidence: 99%